Antiproliferative activity and chemical constituents of Lonchocarpus cultratus (Fabaceae) - Da Silva Landim, E. M.; Ruiz, A. L. T.; De Carvalho, J. E.; Pomini, A. M.; Pastorini, L. H.; Oliveira Santin, S. M.
The aerial parts of L. cultratus were submitted to a phytopharmacological investigation in order to isolate and identify the major secondary metabolites and evaluate its crude extract, fractions and isolated compounds for antiproliferative activity. Seven compounds were isolated and identified as the chalcones 2',4'-dihydroxy-5'-prenylchalcone (1)and isocordoin (2), the flavanone 8-prenylpinocembrin (3), the alkaloid 4-hydroxy-N-methylproline (4), the triterpenes lupeol and lupenone. These compounds were identified by nuclear magnetic resonance of 1H and 13C data in comparison with literature. Hexanic fraction and chalcone 2',4'-dihydroxy-5'-prenylchalcone showed potent results against human cancer cell lines tested.
Keywords: LONCHOCARPUS CULTRATUS; ANTIPROLIFERATIVE ACTIVITY; CHALCONES; FLAVONOIDS